Alcohol, psychiatry and society : comparative and transnational perspectives, c. 1700-1990s - Ernst, Waltraud, 1955-; Müller, Thomas, 1965- (Social histories of medicine., 2022)
The medicalisation of alcohol use has become a prominent discourse that guides policy makers and impacts public perceptions of drinking. This book maps the historical and cultural dimensions of the phenomenon, emphasising medical attitudes to alcohol and the changing perception of consumption in psychiatry and mental health.